Framework for responsive financing of district hospitals of India - Shankar Prinja; Gaurav Jyani; Aarti Goyal; Sameer Sharma; Tarandeep Kaur; Thiagarajan Sundararaman (Frontiers Media S.A., 2024)
IntroductionThe current financing of public-sector district hospitals in India relies on historical budget allocations rather than actual utilization or healthcare needs. We utilized empirical data on healthcare delivery costs to develop the financing framework for these hospitals using a blended payment approach.MethodsThe primary data on cost of delivering services in 27 district hospitals across nine states of India was analysed along with indicators influencing the demand and supply of health services. Payment for outpatient, inpatient, and indirect services was assessed using the risk adjusted global budget, case-based bundled payment, and per-bed-global budget, respectively. Risk adjustment weights were computed by regressing the cost of outpatient care with demand and supply side factors which are likely to influence the utilization or the prices. Budget impact analysis was conducted to assess the fiscal implications of this payment approach, accounting for current care standards and two scenarios: upgrading district hospitals to Indian Public Health Standards (IPHS) or medical colleges.ResultsThe average annual budget for a district hospital in India is estimated at ₹326 million (US$3.35 million), ranging from ₹66 million to ₹2.57 billion (US$0.8-31.13 million). Inpatient care comprises the largest portion (78%) of the budget. Upgrading to IPHS-compliant secondary hospitals or medical colleges would increase average budgets by 131 and 91.5%, respectively.ConclusionImplementing a blended payment approach would align funding with healthcare needs, enhance provider performance, and support ongoing financing reforms aimed at strategic purchasing and universal health coverage.